Global Existence and Decay Estimates of Energy of Solutions for a New Class of p-Laplacian Heat Equations with Logarithmic Nonlinearity - Salah Mahmoud Boulaaras; Abdelbaki Choucha; Abderrahmane Zara; Mohamed Abdalla; Bahri-Belkacem Cheri (Journal of Function Spaces)
The present research paper is related to the analytical studies of p-Laplacian heat equations with respect to logarithmic nonlinearity in the source terms, where by using an efficient technique and according to some sufficient conditions, we get the global existence and decay estimates of solutions.